Feasibility of ecological momentary assessment to study depressive symptoms among cancer caregivers. Issue 5 (28th January 2021) - Shaffer, Kelly M.; Chow, Philip I.; Glazer, Jillian V.; Le, Tri; Reilley, Matthew J.; Jameson, Mark J.; Ritterband, Lee M.
Abstract: Objective: Ecological momentary assessment (EMA) may help with the development of more targeted interventions for caregivers' depression, yet the use of this method has been limited among cancer caregivers. This study aimed to demonstrate the feasibility of EMA among cancer caregivers and the use of EMA data to understand affective correlates of caregiver depressive symptoms. Methods: Caregivers ( N  = 25) completed a depressive symptom assessment (Patient Health Questionnaire‐8) and then received eight EMA survey prompts per day for 7 days. EMA surveys assessed affect on the orthogonal dimensions of valence and arousal. Participants completed feedback surveys regarding the EMA protocol at the conclusion of the week‐long study. Results: Of 32 caregivers approached, 25 enrolled and participated (78%), which exceeded the a priori feasibility cutoff of 55%. The prompt completion rate (59%, or 762 of 1, 286 issued) did not exceed the a priori cutoff of 65%, although completion was not related to caregivers' age, employment status, physical health quality of life, caregiving stress, or depressive symptoms or the patients' care needs ( p s > 0.22). Caregivers' feedback about their study experience was generally positive. Mixed‐effects location scale modeling showed caregivers' higher depressive symptoms were related to overall higher reported negative affect and lower positive affect, but not to affective variability. Conclusions: Findings from this feasibility study refute potential concerns that an EMA design is too burdensome for distressed caregivers. Clinically, findings suggest the potential importance of not only strategies to reduce overall levels of negative affect, but also to increase opportunities for positive affect.